The relationship between task-tecnology fit and job performance : a study of employee in the Bursary, Universiti Teknologi Malaysia (UTM), Skudai / Ainul Basirah Othman - Othman, Ainul Basirah (Faculty of Business and Management, 2013)
This study was conducted to explain the relationship between task-technology fit and job performance. The study was carried out at The Bursary, Universiti Teknologi Malaysia. The study involved 50 respondents with non-academic staff from different categories which include top level management, middle management and lower level management. The researcher studies this topic because to know the relationship between tasks-technology fit and job performance. Moreover, the research objective in this study indicates to identify the relationship task-teclmology fit and job performance among employees in the bursary, Universiti Teknologi Malaysia. In the task-technology fit including eight dimensions which are quality, locatability, authorization, compatibility, production timeliness, system reliability, ease of use/training and relationship with user. In this study, researcher used simple random sampling to define the respondent based on the 147 staffs is the population. In answering research questions that consists eight question, Pearson Correlation were conducted between each task-technology fit's dimensions which is quality, locatability, authorization, compatibility, production timeliness, system reliability, ease of use/training and relationship with user towards job performance.